Psychopathological symptoms in parents and siblings of people on the autism spectrum: A systematic review and meta-analysis. (May 2023) - Bispo-Torres, Ana Cecília; Lucena, Rita; Tavares-Rodrigues, Ivo César; Barouh, Judah L.; Lins-Silva, Daniel H.; Dorea-Bandeira, Ingrid; Souza, Lucca S.; Faria-Guimarães, Daniela; Tolentino, Arthur; Miranda-Scippa, Ângela; Hermens, Daniel F.; Sampaio, Aline S.; et al.
Highlights: Depressive and anxiety symptoms are more common in mothers of children on the autism spectrum (MCAS) than in mothers of neurotypical children. Among families of children on the autism spectrum, mothers scored higher than fathers for depressive and anxiety symptoms. MCAS scored higher by 0.42 standard deviations on the symptom scales when compared with mothers of children with atypical development (e.g. intellectual disabilities, Down Syndrome, Fragile X Syndrome, cerebral palsy, and attention-deficit/hyperactivity disorder). Abstract: Parents and siblings of children on the autism spectrum experience significant distress, and for this reason, it is essential to understand the most prevalent psychopathological symptoms among this population. This work aims to establish the prevalence of psychopathological symptoms in parents and siblings of individuals on the autism spectrum, following the Preferred Reporting Items for Systematic Review and Meta-Analyses Protocols (PRISMA-P) criteria. Searches were carried out using the PubMed/Medline, Embase, PsycINFO, SciELO, and Biblioteca Virtual em Saúde (BVS) databases. Twenty-three articles were included in this review. Depressive symptoms were the most frequently reported conditions, with a higher prevalence in mothers of children on the autism spectrum. In the meta-analysis, mothers of children on the autism spectrum scored higher by 0.42 standard deviations on the symptom scales (SMD 0.42; CI 0.25–0.59), with low statistical heterogeneity (I 2 0%, p  = 0.5) when compared with mothers of children with atypical development. The psychopathological symptoms of relatives should be investigated as part of the follow-up procedures for the child on the autism spectrum to facilitate their treatment.